Coaching and Development of Volleyball Based on Social Skills for Positive Youth Development - Dwi Yulia Nur Mulyadi; Amung Mamun; Berliana Berliana; Tite Juliantine (UNIB Press, 2023)
The holistic approach to developing volleyball skills that incorporates social skills is essential in shaping the character and life skills of young athletes. Social skills such as cooperation, communication, and trust not only impact performance on the field but also shape the morals and values of participants beyond sports. The roles of coaches, teachers, and educators are crucial in guiding students in the world of sports. This study utilized the Quasi Experimental Design